PROPERTIES OF BINDERLESS PARTICLEBOARDS FROM OIL PALM EMPTY FRUIT BUNCH (Elaeis guineensis Jacq.) - Ratri Yuli Lestari (Pusbindiklat - LIPI, 2013)
The objective of this investigation was to evaluate the properties of binderless particleboard from oil palm empty fruit bunches (OPEFB). The pretreatment was boiling in water for 60 minutes and then dried. The dried OPEFB was shredded into fibers and cut into particles (1–5 cm and 6-10 cm). The particles were formed on alluminium foil and then pressed at temperature of 150°C for 10 minutes using pressure of 25 kgf/cm2, 30 kgf/cm2, and 35 kgf/cm2. Particleboard samples were made with a target density of 0.7 g/cm3. The value of density, moisture content, modulus of rupture (MOR), and modulus of elasticity (MOE) were determined based on Japan Industrial Standard (JIS) A 5908: 2003. The particleboards density were 0.566 0.636g/cm3 and the moisture content were 5.17 7.13%. The highest value of MOR and MOE were 2.52 N/mm2 and 223.29 N/mm2. It’s from particleboards with the particle size of 6-10 cm and the pressure of 35 kgf/cm2. The physical properties of particleboards were met the JIS standards while the mechanical properties were not met the standard.